1 - Access to, and Success in, Higher Education in Post-apartheid South Africa: Social Justice Analysis - Adeyemo, Kolawole Samuel; Sehoole, Chika (Journal of Higher Education in Africa, 2022)
The post-apartheid government that came to power in 1994 inherited an inequitable and unjust higher education system whose expression included preferential access to higher education for whites and limited higher educa- tion opportunities for the black majority. As a result, one of the priorities of the new government was to redress the inequalities of apartheid by adopting policies that would widen access to higher education for all South Africans and, simultaneously, ensure their success. This article analyses the progress made in the implementation of equity policies by posing the following ques- tion: ‘What progress has been made in the pursuit of a policy of equity of access and of success since 1997?’ We have examined government-related documents and institutional practices to answer this question. We link ac- cess with success to explain the impact of the transformation agenda on the outcomes of higher education. Using social inclusion and justice theory, we contest neoliberal ideologies of access (Gidlye et al. 2010) as merely increasing participation rates and relying on the economic role of higher education, without paying attention to the factors that should facilitate success in higher education. Methodologically, the paper relies on the documentary analysis of secondary data, on social theory, and on primary data obtained from official government policies and reports.